Gastric polyps and polypoid lesions: Retrospective analysis of 36650 endoscopic procedures in 29940 patients - Vatansever, Sezgin; Akpınar, Zehra; Alper, Emrah; İpek, Serkan and Yazıcıoğlu, Nafi and Ekinci, Neşe and Ünsal, Belkıs (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: The frequency of gastric polyps increases with the widespread use of endoscopy for diagnosis and treatment. As gastric polyps can be malignant or premalignant, histopathological evaluation is needed. The aim of this study is to determine the prevalence and characteristics of gastric polyps in patients undergoing endoscopy. Materials and Methods: This study consisted of a retrospective analysis of 36650 consecutive endoscopy and associated pathology reports of 29940 patients between December 2005 and February 2012 in a tertiary-referral center. Results: Gastric polypoid lesions were detected in 666 (2.22%) patients. Hyperplastic polyps were the most common type of polyps (36.2%), followed by fundic gland polyps (8.3%), inflammatory fibroid polyps (2.4%) and adenomatous polyps (1.9%). Foveolar hyperplasia, neuroendocrine tumor, xanthoma, gastrointestinal stromal tumor, adenocarcinoma and lymphoma were less commonly seen. Malignant transformation was seen in 0.42% of hyperplastic polyps and in 23.1% of adenomatous polyps. Conclusion: Endoscopic appearance of gastric polyps can be variable, distinguishing macroscopically can be misleading. Because of their malignant potential histopathological evaluation is mandatory and polypectomy should be performed whenever possible.